Electrophilic trifluoromethylselenolation of terminal alkynes with Se-(trifluoromethyl) 4-methylbenzenesulfonoselenoate - Ghiazza, Clément; Tlili, Anis; Billard, Thierry (Beilstein Journal of Organic Chemistry, 2017)
Herein the nucleophilic addition of Se-(trifluoromethyl) 4-methylbenzenesulfonoselenoate, a stable and easy-to-handle reagent, to alkynes is described. This reaction provides trifluoromethylselenylated vinyl sulfones with good results and the method was extended also to higher fluorinated homologs. The obtained compounds are valuable building blocks for further syntheses of fluoroalkylselenolated molecules.
Keywords: alkynes; nucleophilic addition; perfluoroalkylselenolation; Se-(trifluoromethyl) 4-methylbenzenesulfonoselenoate; trifluoromethylselenolation